Non-isothermal crystallization kinetics of epoxidized soybean oil on poly (Lactic acid) stereocomplexes - Li, Wenwei; Lu, Xiangli; Kuang, Zhiqiao; Yan, Zhiyong (Edelweiss Applied Science and Technology, 2025)
The crystallization of polylactic acid (PLA) stereocomposites is an effective approach to enhance the mechanical and thermal properties of PLA materials, while epoxidized soybean oil (ESO) has been demonstrated to exhibit good compatibility with PLA. This study prepared composite samples of PLA stereocomposites with ESO via solution blending. The non-isothermal crystallization kinetics of PLA blends were determined using the Jeziorny and Mo methods. Results indicate that the Kc value of SC-PLA-ESO increases with cooling rate, demonstrating accelerated polymer crystallization at higher cooling rates. The non-isothermal crystallization kinetics of PLA blends were investigated using the Jeziorny and Mo methods. Results showed that the Kc value of the SC-PLA-ESO system increased with cooling rate, indicating that the polymer crystallization rate is proportional to the cooling rate. simultaneously, the increase in F(T) values for ESO-containing blends at identical relative crystallinity indicates that ESO enhances the crystallization rate of PLA blends. This conclusion significantly enriches the crystallography theory of PLA.